Concomitant protein pathogenesis in Parkinson’s disease and perspective mechanisms - Han, Yuliang; He, Zhuohao (Frontiers in Aging Neuroscience, 2023)
Comorbidity is a common phenotype in Parkinson’s disease (PD). Patients with PD not only have motor deficit symptoms, but also have heterogeneous non-motor symptoms, including cognitive impairment and emotional changes, which are the featured symptoms observed in patients with Alzheimer’s disease (AD), frontotemporal dementia (FTD) and cerebrovascular disease. Moreover, autopsy studies have also confirmed the concomitant protein pathogenesis, such as the co-existences of a-synuclein, amyloid-beta and tau pathologies in PD and AD patients’ brains. Here, we briefly summarize the recent reports regarding the comorbidity issues in PD from both clinical observations and neuropathological evidences. Furthermore, we provide some discussion about the perspective potential mechanisms underlying such comorbidity phenomenon, with a focus on PD and related neurodegenerative diseases.